2018
DOI: 10.1089/jpm.2018.0011
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Socioeconomic Status, and Healthcare Intensity at the End of Life

Abstract: The effects of minority race/ethnicity on healthcare intensity at the end of life are only partly mediated by other social determinants of health. Future interventions should address the factors driving both direct and indirect effects of race/ethnicity on healthcare intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 25 publications
4
70
1
Order By: Relevance
“…Consistent with Brown et al, 28 we documented extensive racial differences in end-of-life treatment, with Black decedents receiving less hospice care and having more ED visits, hospitalizations, and intensive treatments in the 6 months immediately preceding death compared with White decedents. Although these findings remained even when we accounted for cause of death and other clinical and demographic characteristics in the analysis, we found that racial differences in treatment intensity were especially pronounced among those with noncancer diagnoses.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with Brown et al, 28 we documented extensive racial differences in end-of-life treatment, with Black decedents receiving less hospice care and having more ED visits, hospitalizations, and intensive treatments in the 6 months immediately preceding death compared with White decedents. Although these findings remained even when we accounted for cause of death and other clinical and demographic characteristics in the analysis, we found that racial differences in treatment intensity were especially pronounced among those with noncancer diagnoses.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of more aggressive end-of-life care among decedents of Chinese or South Asian ethnicity is similar to the findings of other large-scale quantitative analyses assessing end-of-life care for people from ethnic minorities in North America such as Hispanic or black people. 16,44,45 Although each ethnic group has multiple unique underlying contributors to these findings, some factors such as provider-patient ethnicity discordance, decreased socioeconomic resources and discrimination may be common to different minority ethnicities. 5,46,47 We found contrasting results with respect to receipt of palliative care in the final 6 months of life, with decedents of South Asian ethnicity less likely, and decedents of Chinese ethnicity more likely, to receive palliative care relative to decedents from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although policies targeting increased hospice enrollment levels for low-income populations with no specific focus on racial/ethnic minority populations would contribute to the economic savings discussed in this article, prior research has indicated that they would not eliminate the racial disparities within hospice enrollment. Brown et al (2018) showed the effects of race/ethnicity on the intensity of end-of-life care are only partly mediated by other social determinants of health. Another study showed removing racial and ethnic disparities is complex and sometimes well-intended reform initiatives might inadvertently reinforce racial/ethnic disparities (Alegria, Alvarez, Ishikawa, DiMarzio, & McPeck, 2016).…”
Section: Discussionmentioning
confidence: 99%